Estudio fenológico y análisis de calidad de semillas de tres especies forestales nativas, promisorias del bosque seco, provincia de Loja - Chamba Romero, Patricia del Rocío (2014)
The dry forest from the south of Ecuador are fragile ecosystems that have been destroyed, due to they located in relatively populated areas that keeps an important economic importance to the rural population, providing timber and non-timber products for the substance. Besides, activities as the livestock and agriculture that performs big pressure on these ecosystems, they have caused a terrible damage in the mountain surface that are covered by degraded soils and very eroded. This is the reality that affects the integrity in the dry forests in the province of Loja, this is the reason for restoring the vegetal cover in these natural ecosystems that have become in an imperative necessity that should be supported in an adequate knowledge of the native flora and fauna and the reproductive biology of the species. The present investigation research was performed with logistic support of The micro propagation vegetal laboratory, “Trough the project generation of propagation protocols for Live In and In vitro elite genotypes of native forest species and promisoristas for reforestation in the region of Ecuador” and it has as a purpose to generate information about the phenology, quality and production of three kinds of forest seeds in the south region of the country. The research was developed in the dry forest of the canton of Zapotillo, Macara and Paltas in the province of Loja, with the next purposes: To determine the time of flowering, fructuacion and defoliation Prosopis sp, Tabebuia billbergii y Loxoterygium huasango; to analyze the relation between phonological phases of three forest species with climatic factors of the área; to determine the productive potential and seed quality analysis at the laboratory of the three forest species by germination of protocols of the International seed Testing Association (ISTA 2007); and disseminating the results of research. The research was performed in two stages: the stage of the camp, that was performed in the community Limones (cantón Zapotillo), Lucarqui – Bramaderos (cantón Paltas) and in the sectors of Vizin and the International Bridge (cantón Macará), located around 200 kilometers of the Loja city; and the stage of the Laboratory of the Vegetal Micropropagation, belonging to the Agropecuary agricultural Area and the Renewable Resources of the National University of Loja. The research was performed in three native species of the dry forest: Prosopis sp, Tabebuia billbergii y Loxopterygium huasango, the investigation was developed with a number of ten and nine trees for each specie. The phenological evaluations in the trees was performed monthly, in Prosopis sp and Loxopterygium huasango, the observations were started in august of 2012 and they finished in july 2013; but in Tabebuia billbergii due to a certain species that show supranual fructuacion (each 2 years) the phenological observations were developed since august 2012 until march 2014. In each evaluated specie was found a productive potential of the fruits and seeds in each tree; and also there were made physics analysis of the seeds such as: weight and seed moisture content, viability, germination energy and germination power. We have as a result that the Prosopis sp shows flowering periods between the months of august to november and fruiting from october to february: in contrast the Loxopterygium huasango the cycle of flowering started since january to april in the and most intence fructuacion occurred between may and june: the periods of flowering and fruiting for Tabebuia billbergii were in the months of january and february. Considering that in this forests there is a determined seasonal rainfall, but the present research shows irregularities in the phenological process of the three species: Prosopis sp shows max flowering stages in this dry season: on the other hand the fruiting of Loxopterygium huasango happened in rainy season and more intense dry season happened in fructuacion; on the other hand Tabebuia billbergii flowering and fructuacion happened in rainy season. The trees of Tabebuia billbergii y Loxopterygium huasango got the most productivity potential with seed from each tree with 766,18 ± 318,79 and 717,41 ± 239,17 grams respectively, the differences of the last species in Prosopis sp was potentially reduced for each tree (289,07 ± 136,19 grams). The obtained results in the present research and the standard evidence of quality of seeds reveal that all the species reached percentages of higher pureness more than the 90 % except the Tabebuia billbergii where the percentage of pureness was of 70,10 %. About the weight, Tabebuia billbergii that had light seeds the weight of 1000 seeds was of 5,30 grams, with a an approximately number of 188679 of seeds in each kilogram; on the other hand the weight of 1000 seeds in Loxopterygium huasango was of 10,10 grams, with a number of 99010 seeds in each kilogram; Prosopis sp got the highest weight with 40,91 grams, but the number of seeds in each kilogram decreased to 24390 units. About the content of humidity all the species showed lower percentages 40 %, we classified the seeds in three species as orthodoxies. In the germination to laboratory level , Prosopis sp reached a high percentage of germination (96,75 %), followed by the Tabebuia billbergii with a percentage of germination of 76,25 % to this two species of germination was quick and relatively homogeneous, due to the ten days of the sowing they showed high percentages of germination energy (51 and 39 % respectively). In other hand the germination of the seeds in Loxopterygium huasango was of 30,25 %, the germination in the seeds in this specie was quite irregular and late (it reached the 21 % of germination energy around 30 days, from the sowing)